Inventarisasi Ekspresi Budaya Tradisional Secara Terstruktur Sebagai Upaya Perlindungan Pengetahuan Tradisional - Novianti, Isti (Jurnal Hukum & Pembangunan, 2015)
Indonesia is a country that has an assortment of tribes and customs. To be observed the diverse cultures that exist so that governments are required to keep to be preserved properly. To know and recognize traditional cultures of various regions will require a data base that includes the traditional knowledge in Indonesia. This database can also be used as a source of information that can be accessed both international and domestic. In this case the central government and regional governments are given the authority to inventory Traditional Cultural Expressions. Effort into making the database has been started in the discourse of the Government in this case the Ministry of Justice and Human Rights Directorate General of Intellectual Property. Although in this case the management of Traditional Cultural Expressions is defensive protection, it is necessary in the wake of the very support system in order to perform such authority, such as what and how the system was created and implemented by the central government and local government? Thus, this paper will discuss the role of government, local government, and institutions that have the authority, namely the Directorate General of Intellectual Property Rights to express the concept of documentation and inventory of Traditional Cultural Expressions structured as efforts to protect Traditional Knowledge.